Indirect Metalinguistic Corrective Feedback and its Effect on Grammar Acquisition in EFL Preservice Teachers at a Chilean University - ortiz, mabel andrea (2019)
This article reveals finding from a study on the impact of indirect metalinguistic corrective feedback on English grammar acquisition. The study followed a pre-experimental design with a sample of 20 third-year students of a Program for Teaching English as a Foreign Language at a  Chilean university. The sample group was asked to write four short argumentative essays for which they received indirect corrective feedback pertaining to grammatical errors observed and then proceeded to rewrite the essays based on the feedback provided. Students were also tested before and after completion of the study, revealing that  the number of grammatical errors in their writing composition significantly declined in the latter situation.